2012
DOI: 10.1175/jcli-d-10-05032.1
|View full text |Cite
|
Sign up to set email alerts
|

East Antarctic Landfast Sea Ice Distribution and Variability, 2000–08

Abstract: This study presents the first continuous, high spatiotemporal resolution time series of landfast sea ice extent along the East Antarctic coast for the period March 2000–December 2008. The time series was derived from consecutive 20-day cloud-free Moderate Resolution Imaging Spectroradiometer (MODIS) composite images. Fast ice extent across the East Antarctic coast shows a statistically significant (1.43% ±0.30% yr−1) increase. Regionally, there is a strong increase in the Indian Ocean sector (20°–90°E, 4.07% ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
215
3
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 149 publications
(226 citation statements)
references
References 153 publications
(331 reference statements)
7
215
3
1
Order By: Relevance
“…(Fraser et al, 2012) demonstrated the presence (and, at times, absence) of multi-year landfast ice to the east of Mill Island, which would facilitate snow ramp formation. SIC-m and trace ions can be seen on a monthly basis here.…”
Section: Influence Of Environmental Signals On the Sea Salt Recordmentioning
confidence: 98%
See 1 more Smart Citation
“…(Fraser et al, 2012) demonstrated the presence (and, at times, absence) of multi-year landfast ice to the east of Mill Island, which would facilitate snow ramp formation. SIC-m and trace ions can be seen on a monthly basis here.…”
Section: Influence Of Environmental Signals On the Sea Salt Recordmentioning
confidence: 98%
“…The The presence of such an ice island presents a strong dynamical barrier to mobile pack ice being advected westward in the coastal current, leading to higher pack ice concentration to the east of this barrier (Fraser et al, 2012).…”
Section: Influence Of Environmental Signals On the Sea Salt Recordmentioning
confidence: 99%
“…Such fast ice is "a preeminent feature of the Antarctic coastal zone and an important interface between the ice sheet and pack ice/ocean" (Fraser et al, 2012). Variability in fast ice extent is often viewed as a sensitive indicator of climate change (Murphy et al, 1995;Heil et al, 2006;Mahoney et al, 2007).…”
Section: Antarctic Sea Icementioning
confidence: 99%
“…This study is the first observational assessment of the change in the GV region after the MGT calving. Sea ice production estimates are presented using a thin ice thickness algorithm based on satellite Special Sensor Microwave/Imager (SSM/I) data and a heat flux calculation [17][18][19] , in conjunction with a fast ice time series and climatology derived from NASA moderate resolution imaging spectroradiometer (MODIS) satellite imagery 20 . We examine the change in sea ice production in 2010 and 2011, relative to the mean annual sea ice production over the preceding years from 2000-2009.…”
mentioning
confidence: 99%